BALANCED NUTRITION EDUCATION FOR TODDLERS - Rokmah, Siti; Karim, Fatmawati; Karimah, Karimah; Melysa, Melysa; Sari, Mela Mustika; Soleha, Sri; Enita, Yani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Mandalahaji Village, located in Pacet Sub-district, lies in the eastern part of Majalaya, Bandung Regency. Based on a preliminary study, the main issue faced by the community is nutrition-related problems. This community service program aims to provide both solutions and education to address these issues, with the goal of controlling the impact and health risks, thereby offering added value to the community. The implementation stages include a preliminary study and site survey, identification of community problems, a pre-implementation phase through network building with partners and stakeholder involvement, implementation of education and community empowerment with local cadres, as well as program evaluation and sustainability management. The results of the program show the delivery of nutrition education and the establishment of a sustainable network of local cadres. This structured community service activity can serve as an alternative solution to the community’s problems through the continuous involvement of stakeholders.